Evaluation of Building Maintenance Quality in Ampel Mosque Surabaya - Agung Sedayu (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2018)
The Ampel Mosque Surabaya East Java Indonesia is a historic mosque that became one of the centers of the spread of Islam in Java by Sunan Ampel. The mosque is a historic site to get attention in care and maintenance on the physical components of the building to prevent the occurrence of damage. This study aims to evaluate the quality of maintenance of Ampel Surabaya mosque building. This study considers social-culture aspects and technical aspects as an instrument to support building maintenance and reliability enhancement. The quality of the maintenance affects the reliability of mosque building construction. The evaluation is done by considering the user's perception of the facility to worship in the mosque of Ampel. The method used is Structural Equation Modeling (SEM). The result of the research shows four variables that make up the model namely: Structural Component, Architectural Component as exogenous manifest variable 2, Quality Maintenance, and Construction Reliability. Relationships between variables indicate a strong level of significance. The path diagram model obtained is explained that the variability of Maintenance Quality is explained by Structural Component and Architectural Component of 81.6%, while Construction Reliability can be explained by Structural Component, Maintenance Quality, and Architectural Component variability of 87.2%. It can be concluded that the influence relationship in the overall model is positive. Ampel mosque management can perform maintenance efforts of mosque building components based on evaluation results and models to calculate the quality of maintenance and reliability of mosque building construction.